Biological control of phytopathogenic fungi by endophytic actinomycetes isolated from maize (Zea mays L.) - Francisco Gheler Costa; Tiago Domingues Zucchi; Itamar Soares de Melo (Brazilian Archives of Biology and Technology, 2013)
This work aimed a survey on the biodiversity of maize endophytic actinomycete, and an evaluation of their potential to control the phytopathogenic fungi. From several regions of São Paulo state, 40 strains were isolated from the healthy maize plants. The identification of these strains, based on morphological properties and fatty acid methyl ester (FAME) profile showed that most of them belonged to the Streptomyces genus. These isolates were first screened for the growth inhibition of phytopathogenic fungi and results showed that all the isolate were able to inhibit the development of at least one tested pathogen. Two selected isolates were then evaluated for the control of P. aphanidermatum in cucumber (Cucumis sativa L.) under greenhouse conditions. Isolate 16R3B was able to reduce up to 71% damping-off incidence whereas isolate 14F1D/2 reduced the disease incidence by 36%. Damping- off control in cucumber, mainly for the isolate 16R3B, suggested for its use in greenhouse cucumber producing fields and to be tested in field trials.